2013
DOI: 10.1371/journal.pone.0077097
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Cytosolic Isocitrate Dehydrogenase as a Negative Regulator of Glucose Signaling for Insulin Secretion in Pancreatic ß-Cells

Abstract: Cytosolic NADPH may act as one of the signals that couple glucose metabolism to insulin secretion in the pancreatic ß-cell. NADPH levels in the cytoplasm are largely controlled by the cytosolic isoforms of malic enzyme and isocitrate dehydrogenase (IDHc). Some studies have provided evidence for a role of malic enzyme in glucose-induced insulin secretion (GIIS) via pyruvate cycling, but the role of IDHc in ß-cell signaling is unsettled. IDHc is an established component of the isocitrate/α–ketoglutarate shuttle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 81 publications
1
51
0
Order By: Relevance
“…Similarly, in INS832/13 cells, Gro3P concentration was calculated to be ∼1.5 mM at 10 mM glucose concentration (31). These cellular concentrations of Gro3P are quite favorable for G3PP/PGP to use this substrate effectively.…”
Section: Gro3p But Not 2-phosphoglycolate Is the Physiologically Relementioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, in INS832/13 cells, Gro3P concentration was calculated to be ∼1.5 mM at 10 mM glucose concentration (31). These cellular concentrations of Gro3P are quite favorable for G3PP/PGP to use this substrate effectively.…”
Section: Gro3p But Not 2-phosphoglycolate Is the Physiologically Relementioning
confidence: 91%
“…The MS was operated in negative electrospray ionization mode using a turbo ion spray source. Transitions used were described previously (31), with additional selected ion monitoring at mass/charge ratios of 154.75/78.79, for 2-PG and glycolate. Quantification was performed as described before (31).…”
Section: Methodsmentioning
confidence: 99%
“…Since this loop parallels, and reenters, the matrix citric acid cycle, it is free of the logistic problems with the pyruvate/citrate cycle discussed above, and could account for the massive increase in citric acid cycle intermediates when glucose is raised. Cytosolic isocitrate dehydrogenase is required for the cycle, but while Jensen et al (240) reported that its suppression partially inhibited GSIS in INS-1 832/13 cells and rat islets, Guay et al (195) came to an opposite conclusion, namely, that IDH1 is a negative regulator of GSIS.…”
Section: Pyruvate/isocitrate Cyclementioning
confidence: 99%
“…These include a glycerolipid/ free fatty acid cycle (15), which generates monoacylglycerol as a coupling factor (16); a phosphoenolpyruvate and mitochondrial GTP-dependent pathway (17,18); and so-called "pyruvate cycles" (19)(20)(21), which export reducing equivalents from the mitochondria to the cytosol. The mitochondrial export of citrate and isocitrate and subsequent engagement of isocitrate with the cytosolic NADP + -dependent isocitrate dehydrogenase (IDH1, hereafter referred to as ICDc) has been shown to regulate insulin secretion (22,23), but the metabolites generated by this pathway that engage with the Insulin secretion from β cells of the pancreatic islets of Langerhans controls metabolic homeostasis and is impaired in individuals with type 2 diabetes (T2D).…”
Section: Introductionmentioning
confidence: 99%